Characteristics of Patients and Their Ascites Who Underwent Repeated Cell‐Free and Concentrated Ascites Reinfusion Therapy. Issue 4 (August 2015) - Maeda, Sayako; Yabuuchi, Junko; Nobuta, Hiroshi; Makiishi, Tetsuya; Hirose, Kunihiko
Abstract Novel cell‐free and concentrated ascites reinfusion therapy (KM‐CART) is easy to use, safe and applicable for refractory ascites. We can get the full amount of ascites, filtrate, and concentrate in a short time. KM‐CART can be applied as palliative care for dying patients including patients with massive malignant ascites. Some patients who underwent repeated KM‐CART survived longer than those who did not repeat the therapy. The aim of this study was to identify the type of patients with ascites for whom KM‐CART would be effective and candidates for repeated KM‐CART. In this retrospective cohort observational study, we examined 123 CART processes performed on 58 patients with refractory ascites. Data were collected before and after processing of the ascites. We compared two groups; patients who underwent KM‐CART ≥ 5 times and those who underwent this process ≤ 4 times. Age, disease, benign or malignant status of the disease, the amount of ascites, concentrations of total protein (TP) and albumin (Alb) and their amounts in the original ascites and the filtered and concentrated ascitic fluid and the recovery ratio of TP and Alb were determined. No significant difference was observed between the two groups in age, disease, amount of ascites, and the recovery ratio of TP and Alb. Significant differences were observed in the amounts of TP and Alb in the original ascites and the filtered and concentrated ascitic fluid. Patients who underwent KM‐CART ≥ 5 times had higher Alb levels in the original ascites than those who underwent this therapy ≤ 4 times. Patients with higher Alb concentrations in the original ascites could be candidates for repeated KM‐CART.